The Side Effect of the Melastoma malabathricum L Ethanol Extract on the Gonad Maturation of Female Orange Mud Crab (Scylla olivacea) - Nuril Farizah; Muhammad Zairin JR; Latifah Kosim Darusman; Arief Boediono; Muhammad Agus Suprayudi (HAYATI Journal of Biosciences, 2018)
The medicinal plants in aquaculture are currently being studied quite extensively by researchers. Medicinal plants can act as an inducer or aphrodisiac and an antifertility agent in gonad maturation. The aimed of the experiment was to known side effects of the herb M. malabathricum L. on maturation process in female mud crab (S. olivacea). This study used 40 crabs with an average weight of 200-250g. The experiment consists of two treatment groups. The controls group (A) that received 100 μl of aquadest and group treatment (B) received 100 μl of 2 mg/g of ethanol extract M. malabathricum L. were studied. For 5, 10, 15, and 20 days of experiment, crabs were anesthetized and sacrified. The ovary was collect for GSI and histology. The end of experiment days (20 day), the hemolymph was collect to used ELISA assay. The result showed, significant differences in treatment group and control groups (p<0.05) in terms the macroscopic morphology of ovary, the mean GSI and the diameter of oocytes. Histological showed the influence of extract M. malabathricum L. on inhibited the ovary development compared with the control groups. Based on this results, it is concluded that ethanol extract of M. malabathricum L. leaves at a dose of 2 mg/g act as an antifertility agent for ovary maturation of S. olivacea.